Treatment of Cancer and Inflammation With Low-Dose Ionizing Radiation - Shuji Kojima; Mitsutoshi Tsukimoto; Noriko Shimura; Hironobu Koga; Akishisa Murata; Tsuyoshi Takara (SAGE Publishing, 2017)
There is considerable evidence from experimental studies in animals, as well as from clinical reports, that low-dose radiation hormesis is effective for the treatment of cancer and ulcerative colitis. In this study, we present 3 case reports that support the clinical efficacy of low-dose radiation hormesis in patients with these diseases. First, a patient with prostate cancer who had undergone surgical resection showed a subsequent increase in prostate-specific antigen (PSA). His PSA value started decreasing immediately after the start of repeated low-dose X-ray irradiation treatment and remained low thereafter. Second, a patient with prostate cancer with bone metastasis was treated with repeated low-dose X-ray irradiation. His PSA level decreased to nearly normal within 3 months after starting the treatment and remained at the low level after the end of hormesis treatment. His bone metastasis almost completely disappeared. Third, a patient with ulcerative colitis showed a slow initial response to repeated low-dose irradiation treatment using various modalities, including drinking radon-containing water, but within 8 months, his swelling and bleeding had completely disappeared. After 1 year, the number of bowel movements had become normal. Interest in the use of radiation hormesis in clinical practice is increasing, and we hope that these case reports will encourage further clinical investigations.